CHAGAS DISEASE IN BRAZIL: EPIDEMIOLOGICAL SURVEILLANCE AND IMPLEMENTATION OF HEALTH POLICIES - Guimarães, Mateus Henrique Dias; Coutinho, Diógenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
Chagas disease, a historical endemic in Latin America, continues to be a significant challenge for public health in Brazil, with 6 to 7 million people infected with Trypanosoma cruzi worldwide. Entomological surveillance and the implementation of public policies are essential to prevent new cases and strengthen the response of the Unified Health System (SUS). This study aims to analyze the operationalization of policies focused on controlling vector transmission and contribute to strengthening prevention and control actions for the disease, which remains socially neglected and invisible. The research, an integrative literature review, selected 10 relevant articles after rigorous inclusion and exclusion criteria. Chagas disease is especially severe in the Northern region of Brazil, where social factors such as poverty and poor sanitary conditions favor its transmission. Surveillance strategies, professional training, educational and intersectoral actions are crucial for controlling the disease, including the Chagas/HIV coinfection.